Educação em direitos humanos: perspectivas decoloniais - Moreira, Messias da Silva (2019)
This work has the pretension to perform a critical analysis from a decolonial prism on the current panorama of Brazilian society regarding education and Human Rights. It originated from a colonizing process based on the domination and exploitation of native peoples and the African Diaspora, for almost four centuries, the time necessary to make a variety of racist, prejudiced, segregating, oppressive, usurping and violent practices like that as naturals and reproducible in a daily basis of the various branches of human action. The genesis of these practices is called Coloniality of Power. This is a consequence of the pattern of power diffused from colonization, supported by the racial classification of society, by false references of race, such as skin color, body and hair forms, characterized as discrimination by phenotypes, which in no ways relates to the questions of reason, cognitive ability, culture, or even superiority or inferiority, nevertheless, it is all related to the various existing power relations and to the formation and consolidation of the economic system that controls the world, the so called capitalism, with its new facet, the neoliberalism. The Coloniality of power has the support in various fields, such as the epistemological, philosophical and religious, all originating from the "epicenter" of human knowledge, Europe (Eurocentrism). Both power relations and the globalized world economic system are responsible for the dehumanization of all, dominant and dominated, oppressors and oppressed, to the point that, more than ever, there is a need for a movement that opposes directly against coloniality of power and knowledge. The Epistemology of the South, the ecology of subaltern knowledge is the proposal of the counter-hegemonic rupture, as it values the plurality of knowledge existing in each locus of enunciation, rescuing identities, knowledge and cultures of different people originating from ancestry. Thus, the different fields of human and social knowledge pertaining to the historical-social totality are re-signified. In order to achieve such macrosocial objective, it is essential to develop cultural practices, which has as a proposal the identification, selfevaluation and self-determination. These practices need to be stimulate by preparing environments for teaching and learning from humanizing disciplines by bringing about behavioral changes and breaking through paradigms. In Brazil, there is the National Plan for Human Rights Education which is the proposal, at the Brazilian legislative level, that stands as the most decolonizing regarding basic education at national level, accompanied by this and aiming to give direction to the political pedagogical school plans were formulated the Guidelines of the National Education and several other legislation aimed at social inclusion, accessibility, combating racism, gender violence and LGBT phobia, which are guided by critical intercultural pedagogy or any other decolonial pedagogy and will provide an environment conducive to coexistence and respect for differences , that is, there is the motivation, the stimulus and favorable environments, only remaining the behavioral change of a whole society, to reach the aggregate product of the social peace paradigm. The research is of the documentary type with bibliographic-investigative methodological procedure. In view of the theme, the present study is directly inserted in the line of research: Society, Knowledge and Education of the Post-Graduation Program in Education of UNIOESTE-PR.